Relación entre las captaciones y colocaciones del Banco Interbank – agencia Iquitos, periodo 2018 – 2022 - Bardales Gil, Ana Paula (2025)
Financial institutions are dedicated to intermediation, so they must ensure that deposits finance loans. The purpose of this thesis is to analyze the behavior of deposits and loans of Banco Interbank - Iquitos Agency during the period 2018 to 2022. This study has a quantitative approach, correlational and non experimental level, concluding that the deposits and loans of Banco Interbank - Iquitos Agency during the study time period, there is a low positive relationship between the deposits and loans of Banco Interbank - Iquitos Agency, during the period 2018 - 2022, because the Correlation coefficient (r) = 0.476372165, is far from 1, which indicates that there is a low positive correlation between the study variables, and that the coefficient of Determination (R2) = 0.226930439, which indicates that the deposits explain the behavior of the placements to a limited extent. For its part, the largest amount raised was recorded in 2020 with an amount of S/ 136,121 thousand, with the "Savings Deposits" type recording the largest balances for the analysis period, in December 2020 and 2021 with amounts of S/ 72,803 and S/ 70,010 thousand respectively. On the other hand, the highest amount placed was recorded in 2020 with an amount of S/ 262,989 thousand, and according to the analyzed trend, direct credit placements showed growth in the first three years of the analysis period, going from S/ 2,780,737 in 2018 to S/ 3,131,932 in 2020, expanding at an average of 6.14% year-on-year, and then contracting, going from 2021 with an amount placed of S/ 3,047,967 to S/ 2,921,663 in 2022, with an average decrease of 3.41%.